Inter-hemispheric asymmetries in high-latitude electrodynamic forcing and the thermosphere during the October 8–9, 2012, geomagnetic storm: An integrated data–Model investigation - Hong, Yu; Deng, Yue; Zhu, Qingyu; Maute, Astrid; Hairston, Marc R.; Waters, Colin; Sheng, Cheng; Welling, Daniel; Lopez, Ramon E. (Frontiers in Astronomy and Space Sciences, 2023)
Inter-hemispheric asymmetry (IHA) in the Earth’s ionosphere-thermosphere (IT) system can be associated with high-latitude forcing that intensify during storm-time, e.g., ion convection, auroral electron precipitation, and energy deposition, but a comprehensive understanding of the pathways that generate IHA in the IT is lacking. Numerical simulations can help address this issue, but accurate specification of high-latitude forcing is needed. In this study, we utilize the Active Magnetosphere and Planetary Electrodynamics Response Experiment revised field-aligned currents (FACs) to specify the high-latitude electric potential in the Global Ionosphere and Thermosphere Model (GITM) to examine the IHA in the IT system during the October 8-9, 2012 storm. This study illustrates the advantages of the FAC-driven technique, the realistic pattern-driven simulation better captures the high-latitude ion drift and convection distribution compared to empirical model-driven case. The cross-polar-cap potential, hemispheric power and convection equatorial boundary show significant IHAs with a clear By dependence in the convection boundary. Comparison with mirrored precipitation-based convection suggests that the convection distribution is more likely determined by R2 FAC edge, while its strength also depends on the ionospheric conductance associated precipitation. FAC-driven simulation can also capture the storm-time neutral density response observed by the Gravity field and steady-state Ocean Circulation Explorer satellite on the dusk-side. The IHA in the neutral density response closely follows the IHA in the total Joule heating dissipation with a time delay about 3 hours. More Joule heating associated with greater high-latitude electric potential in the southern hemisphere suggests that the high-latitude forcing could become the dominant factor to IHAs in the thermosphere when near the equinox. Our study improves the understanding of storm-time IHA in the high-latitude forcing and the IT system.